Does university students prefer printed reference book over online materials? A case study of private higher learning institution / Mustaffa, M. H., Mohd, S. I. and Haron, H. - M. H., Mustaffa; S. I., Mohd; H., Haron (Universiti Teknologi MARA, Perlis, 2021)
The sole purpose of a resource center or library in any higher education institution is to enhance a learning environment and support teaching, learning and research activities. Over the years, higher education institutions keep on increasing their possession of reference material in them of reference materials in their libraries for the use of students, academics and staff that include both printed and online materials. Due to this fact, it is a goal of every library to ensure that those materials are fully utilized by its users. However, with the growth of electronic facilities and resources in libraries, it is time to determine the factors that influence users’ library materials preference. This study adopts a descriptive research design with survey samples from the Universiti Teknologi PETRONAS. Our study reveals that users’ perceived usefulness and perceived ease of use play a crucial role to influence their intention to choose a library resource format where attitude fully mediates the relationship between these variables. This study also identified a partial mediating effect of desire between users’ attitudes and intentions. It also found that organizational characteristics have a significant effect on users’ perceived usefulness and perceived ease of use. Overall, by focusing on the underlying mechanisms of the theories TAM, TPB, and TSR in library resource format choosing behaviour context this study proposes an integrated model, contributes to both theories, and practices in library management.